THE STRUCTURE OF THE PROJECTIVE COMPETENCE: CHARACTERISTICS OF CONTENT AND COMPONENTS - Özbaş, M.; Kassen, G. A.; Mukhatayeva, D. I. (Farabi Journal of Social Sciences, 2018)
The projective activity is one of the main activities of the graduates along with scientific-research and organizational-administrative ones. Therefore, the formation of the projective competence of the students is a topical problem in the system of university education. The article analyzes the content, the componential structure and the nomenclature of the skills and abilities of the projective competence necessary for the students. The analysis of the various scientific and pedagogical sources shows that the the problem of the projective competence formation in the future specialists is not developed sufficiently. The authors demonstrate the results of the questioning, which formed the basis of four components of the projective competence: administrative, emotionally personal, creative and intellectual. The respondents were the graduates and undergraduates of the “Pedagogics and Psychology”, “Social Pedagogics and Self-cognition specialties. The total number was 52 persons. The substantial analysis of the questionnaires allowed to group each component of the projective competence with the help of skills and abilities selected by students. The interesting answers were the answers, which demanded the selection of the strong and weak points in the formation of the projective competence on the basement of self-assessment. At the same time, any of the “strong” points did not collect even a third of the respondentst, which testified the necessity of the formation of the projective competence, since it would not be developed spontaneously on the basis of the increasing of the quantitative or age characteristics of the students. The results of the questioning showed a peculiar awareness of the graduates and undergraduates about comprehension of the content of the projective competence and its importance for the future professional activity. At the same time there is an extreme necessity of the social and pedagogical support for the formation of the main components of the projective competence within the frame of the university education. The forms of the support have to be harmoniously included into educational and extracurricular activities of the students. Key words: competence-based paradigm, characteristics of content, competence-based model of education, projective activity, projective competence, demand of the specialists, administrative skills, efficiency, social and pedagogical support, the process of the formation of the projective competence.